SIMULATION OF COMMUNICATIVE SITUATIONS OF MEANS OF FORMATION OF STUDENTS 'READINESS FOR FOREIGN COMMUNICATION (Pedagogy of Higher and Secondary Education, 2001)
The article deals with the question of making the models of communicative situations during English classes at the Pedagogical University as the means of forming students’ preparedness to communicate using a foreign language.